Fibro-Osseous Lesions of the Skull Base in the Pediatric Population - Wilson, Meghan; Snyderman, Carl (Journal of Neurological Surgery Part B: Skull Base, 2018)
Fibro-osseous lesions of the skull base include a variety of lesions with different biologic behavior. The most common lesions include fibrous dysplasia, osteoma, aneurysmal bone cyst, and juvenile ossifying fibroma. The diagnosis can usually be established with radiographic imaging. In the absence of symptoms, slow-growing lesions can often be observed. When surgery is indicated for relief of symptoms, endoscopic endonasal techniques are well suited for all age groups.
Keywords: fibro-osseous lesions; fibrous dysplasia; osteoma; aneurysmal bone cyst; juvenile ossifying fibroma; endoscopic endonasal surgery; skull base